Late-Onset Pompe Disease with Nemaline Bodies. (27th September 2018) - Frezza, E.; Terracciano, C.; Giacanelli, M.; Rastelli, E.; Greco, G.; Massa, R.
Abstract : Pompe disease is an autosomal recessive disorder characterized by deficiency of alpha-glucosidase, a lysosomal enzyme, which can lead to glycogen accumulation in skeletal muscle, heart, and nervous system. Clinical presentation is highly variable, with infantile and late-onset (LOPED) forms. Although muscle biopsy findings are rather stereotyped, atypical features have been described. A 52-year-old man without a family history of muscle disorders presented with slowly progressing upper and lower limb girdle weakness and hyperCKemia. At needle EMG, a diffuse neurogenic pattern was detected. Muscle biopsy showed a selective type 1 fiber atrophy with vacuoles of various sizes, filled with PAS and acid phosphatase positive material, confirmed to be glycogen by electron microscopy (EM). Many atrophic fibers contained foci of myofibrillar material recognized as nemaline bodies (NBs) at EM. Low level of alpha-glucosidase activity in blood and molecular genetic testing confirmed the diagnosis of late-onset Pompe disease (LOPED). Major causes of hereditary and acquired NB myopathy were ruled out. In conclusion, NBs represent a novel histological finding in LOPED and characterize the atypical presentation of our case.